Evaluating ten spectral vegetation indices for the identification of military underground structures - Melillos, George; Themistocleous, Kyriacos; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2019)
Ten, widely-used vegetation indices (VIs), were evaluated for their ability to identify military underground structures. During this study, several ground spectroradiometric campaigns took place, in a fenced military area in Cyprus, cultivated with barley crops, during a complete phenological cycle (2016-2017). A SVC HR-1024 field spectroradiometer was used and in-band reflectances were determined for medium and high resolution satellite sensors, including Landsat 8. The measurements were taken at the following test areas: (a) vegetation area covered with the vegetation (barley), in the presence of an underground military structure (b) vegetation area covered with the vegetation (barley), in the absence of an underground military structure. The test areas were identified, analyzed and modelled under different scenarios. All vegetation indices were evaluated for their separability performance, and the results were presented through image maps.
Keywords: Crop marks; Cyprus; Ground spectroscopy; Remote Sensing; Vegetation indices